Towards a natural classification of Dothideomycetes 6: The genera Dolabra, Placostromella, Pleosphaerellula, Polysporidiella and Pseudotrichia (Dothideomycetes incertae sedis) - Thambugala, Kasun M.; Ariyawansa, Hiran A.; Liu, Zuo-Yi; Chukeatirote, Ekachai; Hyde, Kevin D. (Phytotaxa, 2014)
The type specimens of Dolabra, Placostromella, Pleosphaerellula, Polysporidiella and Pseudotrichia were re-examined in order to suggest their familial and higher placement according to the morphology based on modern taxonomic concepts. An overview of the history and descriptions and illustrations of these genera are provided. Based on morphological similarities, Placostromella is placed in Parmulariaceae, while Pseudotrichia is transferred to Montagnulaceae. Pleosphaerellula is placed in Pleosporales, genera incertae sedis and Polysporidiella is retained in Dothideomycetes, genera incertae sedis as it is not typical of any existing family of Dothideomycetes. According to published phylogenetic data, Dolabra belongs in Chaetothyriomycetidae, genera incertae sedis (Eurotiomycetes). Recollection, epitypifycation and multi-gene molecular analyses are needed for all type species of these genera in order to clarify their familial status. By illustrating and redescribing the type species we expect to stimulate interest for these fungi to be recollected.